Predicting the direction, maximum, minimum and closing prices of daily Bitcoin exchange rate using machine learning techniques - Mallqui, Dennys C.A.; Fernandes, Ricardo A.S. (Applied soft computing, 2019)
Bitcoin is the most accepted cryptocurrency in the world, which makes it attractive for investors and traders. However, the challenge in predicting the Bitcoin exchange rate is its high volatility. Therefore, the prediction of its behavior is of great importance for financial markets. In this way, recent studies have been carried out on what internal and/or external Bitcoin information is relevant to its prediction. The increased use of machine learning techniques to predict time series and the acceptance of cryptocurrencies as financial instruments motivated the present study to seek more accurate predictions for the Bitcoin exchange rate. In this way, in a first stage of the proposed methodology, different feature selection techniques were evaluated in order to obtain the most relevant attributes for the predictions. In the sequence, it was analyzed the behavior of Artificial Neural Networks (ANN), Support Vector Machines (SVM) and Ensemble algorithms (based on Recurrent Neural Networks and the k-Means clustering method) for price direction predictions. Likewise, the ANN and SVM were employed for regression of the maximum, minimum and closing prices of the Bitcoin. Moreover, the regression results were also used as inputs to try to improve the price direction predictions. The results showed that the selected attributes and the best machine learning model achieved an improvement of more than 10%, in accuracy, for the price direction predictions, with respect to the state-of-the-art papers, using the same period of information. In relation to the maximum, minimum and closing Bitcoin prices regressions, it was possible to obtain Mean Absolute Percentage Errors between 1% and 2%. Based on these results, it was possible to demonstrate the efficacy of the proposed methodology when compared to other studies. •We predict the Bitcoin price direction and forecast the Bitcoin exchange rates (maximum, minimum and closing prices), considering daily data.•The proposed methodology is based on the analysis of attribute selection methods combined with machine learning algorithms to predict the Bitcoin exchange rates.•Machine Learning Ensemble algorithms are proposed, where the combination of Recurrent Neural Networks and a Tree classifier obtained the best results to predict the Bitcoin price direction.•The SVM algorithm obtained the best results to forecast the Bitcoin exchange rates.•The proposed methodology provides very good results when compared to the state-of-the-art studies.